Answer:
(2, 0, - 2 )
Explanation:
4x - 2y + z = 6 → (1)
- 2x + y = - 4 → (2)
3y - 2z = 4 → (3)
multiplying (2) by 2 and adding to (1) will eliminate both x and y
- 4x + 2y = - 8 → (4)
add (1) and (4) term by term to eliminate x and y
0 + 0 + z = - 2
z = - 2
substitute z = - 2 into (3) and solve for y
3y - 2(- 2) = 4
3y + 4 = 4 ( subtract 4 from both sides )
3y = 0 ⇒ y = 0
substitute y = 0 into (2) and solve for x
- 2x + 0 = - 4
- 2x = - 4 ( divide both sides by - 2 )
x = 2
solution is (2, 0, - 2 )